Catalytic evaluation of nanoflower structured manganese oxide electrocatalyst for oxygen reduction in alkaline media - Han, S.J. (MDPI, 2020)
An electrochemical nanoflowers manganese oxide (MnO2) catalyst has gained much interest due to its high stability and high specific surface area. However, there are a lack of insightful studies of electrocatalyst performance in nanoflower MnO2. This study assesses the electrocatalytic performances of nanoflower structure MnO2 for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in a zincâair battery as a bifunctional electrocatalyst. The prepared catalyst was characterized in term of morphology, crystallinity, and total surface area. Cyclic voltammetry and linear sweep voltammetry were used to evaluate the electrochemical behaviors of the as-prepared nanoflower-like MnO2. The discharge performance test for zincâair battery with a MnO2 catalyst was also conducted. The results show that the MnO2 prepared at dwell times of 2, 4 and 6 h were nanoflowers, nanoflower mixed with nanowires, and nanowires with corresponding specific surface areas of 52.4, 34.9 and 32.4 g/cm2, respectively. The nanoflower-like MnO2 catalyst exhibits a better electrocatalytic performance towards both ORR and OER compared to the nanowires. The number of electrons transferred for the MnO2 with nanoflower, nanoflower mixed with nanowires, and nanowire structures is 3.68, 3.31 and 3.00, respectively. The as-prepared MnO2 nanoflower-like structure exhibits the best discharge performance of 31 higher than the nanowires and reaches up to 30 of the theoretical discharge capacity of the zincâair battery. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.